Photoresponsive, switchable, pressure-sensitive adhesives: influence of UV intensity and hydrocarbon chain length of low molecular weight azobenzene compounds. Issue 59 (22nd November 2021) - Lee, Tae-Hyung; Han, Gi-Yeon; Yi, Mo-Beom; Shin, Jae-Ho; Kim, Hyun-Joong
Abstract : A photoresponsive switchable pressure-sensitive adhesive (PSA) was fabricated with an azobenzene-containing polymer and low molecular weight compounds. Its adhesion force was activated/deactivated rapidly by UV/visible light irradiation. Abstract : Unlike traditional adhesives with a fixed adhesive force, switchable adhesives, which have an adhesive force that can be adjusted by external stimuli, are specifically designed to be released according to user demand, or to enable the transfer of fine electronic devices. Previously developed switchable adhesives have limitations such as a slow switching rate, narrow adhesion modulation range, or the lack of reusability. Thus, we fabricated switchable pressure-sensitive adhesives (PSAs) that can overcome these limitations. The adhesive force of each switchable PSA, which comprises an azobenzene-containing acrylic polymer and low molecular weight compounds, was designed to be activated/deactivated via ultraviolet (UV) and visible light irradiation. The adhesive force and UV intensity required for the switch were found to be dependent on the aliphatic chain length of the compound. The adhesive force of the SP-C10, i.e., a switchable PSA containing a azobenzene compound with an aliphatic chain of 10 hydrocarbons, increased to 3.5 N from nearly zero in response to only 30 s of low-level (25 mW cm −2 ) UV irradiation. Additionally, SP-C10 did not lose its adhesive force even after 30 cycles of repeated adhesion switching. The mechanism of adhesion switching influenced by UV intensity and the structure of low molecular weight azobenzene compounds are also reported.